A Qualitative Study on Nonverbal Communication in Healthcare Facilities Based on Patients' Experiences (Third Sector Social Economic Review, 2026)
This study aims to examine the organizational communication and behavioral dimensions of nonverbal communication in healthcare services based on patients' experiences. The study analyzes the impact of nonverbal elements such as body language, eye contact, smiling, touching, and tone of voice in the interactions experienced between healthcare professionals and patients on trust, satisfaction, and perceived quality of healthcare services. A phenomenological design was adopted in this qualitative research study. Data obtained from semi-structured interviews with patients receiving healthcare services in the provinces of Kırklareli, Tekirdağ, and Istanbul were analyzed using the thematic analysis method with MAXQDA 2024 software. The findings reveal that nonverbal communication is considered a decisive factor in patients' perception of trust, sincerity, and professionalism, while negative nonverbal behaviors are associated with loss of trust and feelings of worthlessness. The study emphasizes that nonverbal communication is a critical tool in improving communication quality in healthcare services and strengthening organizational behavior processes. Attention is drawn to the need to strengthen communication training in healthcare organizations, monitor interaction processes through feedback mechanisms, develop in-service awareness programs, and include nonverbal communication indicators in performance evaluation systems. Nonverbal communication's ability to reveal the context of perceived service quality and organizational behavior in healthcare services provides the study with a unique contribution based on the patient perspective. The research results offer practical managerial recommendations for developing a patient-centered service approach and reveal the need to systematically address nonverbal elements in patient-focused communication strategies.
Keywords: Nonverbal Communication; Patient Experience; Organizational Behavior; Healthcare Organizations; Healthcare Services